2022
DOI: 10.33584/jnzg.2021.83.3501
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from New Zealand sheep and beef farms

Abstract: This project aimed to develop a dataset containing animal policies, production efficiencies, and greenhouse gas (GHG) emissions of a large number of sheep and beef farms, and to examine the relationships between farm management and farm physical constraints, and GHG emissions. We used the farm-scale model Farmax to estimate feed inventories, livestock policies and GHG emissions of 170 New Zealand sheep and beef farms. Emissions were calculated from Farmax outputs using Agricultural Inventory methodology. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
0
0
Order By: Relevance
“…However, comparison can be made using the yield of GHG per kg DM eaten. For example, the output of animal GHG emissions from dry-matter intake using the standard calculation method in this study is approximately 0.65 kg CO 2 -e/kg DM, similar to the 0.67 kg CO 2 -e/kg DM that can be calculated from data reported by Vibart et al (2021) for low-intensity sheep and beef farming.…”
Section: Discussionsupporting
confidence: 82%
“…However, comparison can be made using the yield of GHG per kg DM eaten. For example, the output of animal GHG emissions from dry-matter intake using the standard calculation method in this study is approximately 0.65 kg CO 2 -e/kg DM, similar to the 0.67 kg CO 2 -e/kg DM that can be calculated from data reported by Vibart et al (2021) for low-intensity sheep and beef farming.…”
Section: Discussionsupporting
confidence: 82%
“…The per hectare GHG emission from the pastoral area increased in 2020/21 due to a higher stocking rate, but the whole farm figure decreased due to a lesser area in pasture. By comparison, the average gross GHG emission from the North Island Class 4 farm is 3.9 tonnes CO 2 e/ha, or a gross total of 1,693 tonnes CO 2 e, with a range of gross emissions across this farm class from 2.1-5.9 tonnes CO 2 e/ha (Vibart et al 2020). The carbon sequestration from the trees assumes that the conifers are eligible for the new averaging scheme 1 OverseerFM file for Pukekauri, based on whole property area.…”
Section: Resultsmentioning
confidence: 99%
“…In a related study, Neal and Roche (2020) looked at profitability and resilience of pasture-based dairy farms and found that greater profit was associated with more home-grown pasture and crop eaten, higher stocking rates, higher production per cow and lower farm working expenses. The efficiency of pasturebased dairy systems is largely driven by annual pasture production, pasture utilisation and feed conversion (Vibart et al, 2012). The correlation between methane emissions and profit poses a challenge to the industry's effort to reduce methane whilst increasing or maintaining profit.…”
Section: Exploring Modifications To Case Study Farmsmentioning
confidence: 99%